Kedudukan Akta Notaris dalam Penyelesaian Sengketa Penghapusan Merek di Luar Pengadilan - Bella Nova Iskandar (Program Studi Kenotariatan Fakultas Hukum Universitas Pelita Harapan, 2021)
Recently, various types of disputes can arise in the community. In resolving these disputes, the disputing parties are given the freedom to choose the dispute resolution forum according to their wishes. Non-court dispute resolution schemes are strengthened by Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Juridically, the mechanism of brand dispute resolution can be done through litigation in the Commercial Court, as well as non-litigation by using an alternative mechanism for dispute resolution, either through arbitration, negotiation, mediation, conciliation, or other ways agreed upon by both parties of the dispute. The final result of the parties' dispute settlement agreement is resolution which is poured into a form of peace treaty made before a Notary. To see the position of the notarial deed in resolving disputes over brand deletions outside court, especially in the dispute over the